Difficult conversations : how to discuss what matters most - Stone, Douglas, 1958-; Patton, Bruce; Heen, Sheila (Penguin Books, 2023)
"The 10th-anniversary edition of the New York Times business bestseller-now updated with "Answers to Ten Questions People Ask" We attempt or avoid difficult conversations every day-whether dealing with an underperforming employee, disagreeing with a spouse, or negotiating with a client. From the Harvard Negotiation Project, the organization that brought you Getting to Yes, Difficult Conversations provides a step-by-step approach to having those tough conversations with less stress and more success. you'll learn how to: ʺ Decipher the underlying structure of every difficult conversation ʺ Start a conversation without defensiveness ʺ Listen for the meaning of what is not said ʺ Stay balanced in the face of attacks and accusations ʺ Move from emotion to productive problem solving"--